Development of dialogue system architecture toward co-creating social intelligence when talking with a partner robot - Fujii, Ayaka; Jokinen, Kristiina; Okada, Kei; Inaba, Masayuki (Frontiers in Robotics and AI, 2022)
Social robots have grown increasingly integrated into our daily lives in recent years. Robots can be good social agents who engage with people, such as assistants and counselors, and good partners and companions with whom people can form good relationships. Furthermore, unlike devices such as smart speakers or virtual agents on a screen, robots have physicality, which allows them to observe the actual environment using sensors and respond behaviorally with full-body motions. In order to engage people in dialogue and create good relationships with robots as close partners, real-time interaction is important. In this article, we present a dialogue system platform developed with the aim of providing robots with social skills. We also built a system architecture for the robot to respond with speech and gestures within the dialogue system platform, which attempts to enable natural engagement with the robot and takes advantage of its physicality. In addition, we think the process called “co-creation” is important to build a good human–robot interaction system. Engineers must bridge the gap between users and robots in order for them to interact more effectively and naturally, not only by building systems unilaterally but also from a range of views based on the opinions of real users. We reported two experiments using the developed dialogue interaction system with a robot. One is an experiment with elderly people as the initial phase in this co-creation process. The second experiment was conducted with a wide range of ages, from children to adults. Through these experiments, we can obtain a lot of useful insights for improving the system. We think that repeating this co-creation process is a useful approach toward our goal that humans and robots can communicate in a natural way as good partners such as family and friends.